2015
DOI: 10.1111/bju.13334
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and its components among men with and without clinical benign prostatic hyperplasia: a large, cross‐sectional, UK epidemiological study

Abstract: ObjectivesTo compare the prevalence of metabolic syndrome and the components of metabolic syndrome in men aged ≥50 years with and without clinical benign prostatic hyperplasia (BPH). Subjects and MethodsThis was a cross-sectional study using the UK Clinical Practice Research Datalink (CPRD). Men were selected from the CPRD who were aged ≥50 years and still registered as of 31 December 2011. Cohort 1 included men with clinical BPH, and cohort 2 men without clinical BPH who were matched 1:1 to those in cohort 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
4
36
1
Order By: Relevance
“…On the other hand, Zoe et al reported higher PSA levels in BPH patients with MtS (23). Our findings were not in the same line with DiBello et al (22) but, were similar with results of Zou et al (23). There was higher PSA levels in Group 1 than in Group 2 without statistical significance.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, Zoe et al reported higher PSA levels in BPH patients with MtS (23). Our findings were not in the same line with DiBello et al (22) but, were similar with results of Zou et al (23). There was higher PSA levels in Group 1 than in Group 2 without statistical significance.…”
Section: Discussionsupporting
confidence: 84%
“…DiBello et al reported BPH and MtS association with elevated PSA levels and these could indirectly connect with decreased odds of having MtS and its components (22). On the other hand, Zoe et al reported higher PSA levels in BPH patients with MtS (23).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MS in this study is less than what researchers from western world [31][32][33][34] and Asia 30 found. Their studies however were conducted in the urban centres.…”
Section: Prevalence Of Metabolic Syndromecontrasting
confidence: 82%
“…14 Studies have also shown consistently that the prevalence of MS increases with age 23,27,31,32,43 Some Nigerian studies found a prevalence of between 10%-35.42% among the general populace. 18,20,21 Specifically, Ulasi et al 18 and Similayi et al 21 using IDF and ATP criteria found a prevalence of between 10.0%-23.19% in suburban centres.…”
Section: Prevalence Of Metabolic Syndromementioning
confidence: 97%
See 1 more Smart Citation